Website Pemerintah Daerah sebagai Sarana Online Public Relations - Liliek Budiastuti Wiratmo; Noor Irfan; Kuwatono Kuwatono (Jurnal Aspikom, 2017)
New media allows anyone to produce, reproduce, distribute, and access various kinds of messages and uses, including online Public Relations (Online PR). This study aims to analyze websites of local governments (district and the city) as a means of Online PR and to find model of utilization Online PR. This study uses qualitative method reinforced by benchmarking of functional between government website management and service display. The results  show a model of utilization of local government website as a tool for online PR.